2016
DOI: 10.7475/kjan.2016.28.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Patients with Multiple Myeloma

Abstract: Purpose:The purpose of this study was to identify the quality of life reported by patients with multiple myeloma and secondly to identify the factors that impact the quality of life (QoL). Methods: 189 patients with multiple myeloma completed survey questionnaires. Quality of life was evaluated using European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core (EORTC QLQ-C) 30 and Multiple Myeloma (MY) 20. The data were analyzed using the t-test, ANOVA, Kruskal-Wallis test, Dun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…It is suggested that evidence-based nursing can reduce the anxiety and depression mental state of patients with multiple myeloma. The reason for analysis is that evidence-based nursing affects the related factors of patients' psychological resilience through intervention, and eliminates or alleviates the psychological impact of unfavorable factors, such as direct comfort and encouragement, helping patients fight for social support, etc, which is conducive to alleviating adverse psychological states [12][13][14]. After the implementation of evidence-based nursing, the basic nursing, specialist nursing, critical care, ward management, and health education nursing quality evaluation are higher than before implementation.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that evidence-based nursing can reduce the anxiety and depression mental state of patients with multiple myeloma. The reason for analysis is that evidence-based nursing affects the related factors of patients' psychological resilience through intervention, and eliminates or alleviates the psychological impact of unfavorable factors, such as direct comfort and encouragement, helping patients fight for social support, etc, which is conducive to alleviating adverse psychological states [12][13][14]. After the implementation of evidence-based nursing, the basic nursing, specialist nursing, critical care, ward management, and health education nursing quality evaluation are higher than before implementation.…”
Section: Discussionmentioning
confidence: 99%